Structure of Neisseria meningitidis lipoprotein GNA1162. Issue 4 (2nd April 2013) - Cai, Xiangyu; Lu, Jing; Wu, Zhenhua; Yang, Chunting; Xu, Honglin; Lin, Zhijie; Shen, Yuequan
<x xml:space="preserve">Abstract</x> GNA1162, a predicted lipoprotein from Neisseria meningitidis, is a potential candidate for a universal vaccine against meningococcal disease caused by N. meningitidis serogroup B. Here, the crystal structure of GNA1162 at 1.89 Å resolution determined by single‐wavelength anomalous dispersion (SAD) is reported. The structure of GNA1162 appears to be a dimer in the crystallographic asymmetric unit as well as in solution. The overall structure of the dimer indicates that each monomer inserts its C‐terminal α5 helix into the hydrophobic groove of the other molecule. Moreover, the β4 strands of each monomer lie antiparallel to each other and interact through multiple main‐chain hydrogen bonds. Through structural comparisons and operon predictions, it is hypothesized that GNA1162 is part of a transport system and assists in transport and reassembly. The crystal structure of GNA1162 sheds light on its possible function and provides potentially valuable information for the design of a vaccine against meningococcal disease.